PKP-005 Prognostic impact of novel gene polymorphisms in newly diagnosed acute myeloid leukaemia adults undergoing induction chemotherapy. (24th March 2015) - Megías Vericat, J; Montesinos, P; Herrero, M; Moscardó, F; Bosó, V; Martínez-Cuadrón, D; Rojas, L; Aliño, S; Sanz, M; Poveda, J
Abstract : Background: Single nucleotide polymorphisms (SNPs) could lead to inter-individual differences in treatment outcomes. Purpose: A recent study 1 reported several novel SNPs involved in cytarabine cytotoxicity using a whole-genome approach, which were associated with clinical outcomes in a paediatric AML population. However their association with effectiveness and toxicity remain undetermined in adults. Material and methods: The six SNPs with clinical significance in the Gamazon study 1 (Table 1) were evaluated in 109 adult patients at initial diagnosis with AML using a mass spectrometry–based multiplex genotyping assay (Sequenom). All patients were treated with idarubicin plus cytarabine. Genotypes were grouped as dichotomous variables (dominant/recessive model). Efficacy was evaluated comparing complete remission (CR) vs. partial remission or resistance. Toxicities were grouped as binary variables (grade: 0–1 vs. grade: 2–4, Who scale). Haematological toxicity was measured with the time to neutropenia/thrombocytopenia recovery since first day of chemotherapy. Variables were assessed using χ 2 and Mann–Whitney U tests. Results: The median age of patients was 53 years (17–78 years). Among the baseline characteristics analysed (age, gender, haemoglobin, leukocyte, platelet and peripheral or BM blasts count) there was significant difference in genotype distributions regarding age (wild allele carriers of rs9883101 were older, p = 0.02) and gender (men had a higher proportion of variant alleles for rs6550826 and rs7729269, p = 0.003 and 0.006; and wild allele for rs2897047, p = 0.005). Toxicities were more frequent with variant alleles of several SNPs (table), but they were not associated with the CR rates. Conclusion: We obtained new associations of these novel polymorphisms with toxicity, not previously studied in adult AML patients, but not in effectiveness. These SNPs could be useful biomarkers in clinical practice. Reference: Gamazon ER, Lamba JK, Pounds S, et al . Comprehensive genetic analysis of cytarabine sensitivity in a cell-based model identifies polymorphisms associated with outcome in AML patients. Blood 2013;121(21):4366–76 No conflict of interest.